Sense and sensibility - Lee, Ang 1954-; Thompson, Emma; Winslet, Kate; Grant, Hugh; Rickman, Alan; Austen, Jane 1775-1817 (Columbia Tristar Home Video, 1999)
When Mr. Dashwood dies, he must leave the bulk of his estate to the son by his first marriage, which leaves his second wife and three daughters (Elinor, Marianne, and Margaret) in straitened circumstances. They are taken in by a kindly cousin, but their lack of fortune affects the marriageability of both practical Elinor and romantic Marianne. When Elinor forms an attachment for the wealthy Edward Ferrars, his family disapproves and separates them. And though Mrs. Jennings tries to match the worthy (and rich) Colonel Brandon to her, Marianne finds the dashing and fiery Willoughby more to her taste. Both relationships are sorely tried. But this is a romance, and through the hardships and heartbreak, true love and a happy ending will find their way for both the sister who is all sense and the one who is all sensibility.